Plasma hypertonicity in children. - Teixeira, Ana (2010)
The plasma hypertonicity is a severe and quite frequent disorder in children. The most frequent causes are hypernatremia related conditions, even though other causes of hyperosmolarity, such as hyperglycaemia and exogenous solutes accumulation also occur. The management and treatment of this condition is delicate and requires a thorough understanding of the underlying hydro electrolytic disorder. The authors perform a theoretical review of plasma hypertonicity in children, focusing on the three most frequent associated conditions: hypernatremic dehydration, salt poisoning and hyperosmolar coma.